(untitled) (Research, Society and Development, 2022)
Objective: To identify the consequences on breastfeeding resulting from exposure to passive smoking during pregnancy. Methodology: Systematic literature review based on the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) method, carried out in the electronic databases ScieLo, PubMed, Scopus and Web of Science, using the following descriptors: “secondhand smoke”, “pregnancy”, “pregnant women” and “breastfeeding”. Full articles, available in Portuguese, English or Spanish, published between January 2010 and October 2021 and which have statistical significance applied to the results were included. Results: Seven articles made up the final sample of this study. All studies were prospective cohorts, presenting level of evidence III (moderate). Most of the pregnant women were exposed to tobacco smoke in their homes, reiterating the information that cigarette smoke could come from close family members. Maternal exposure to passive smoking during pregnancy was significantly associated with an increase in stopping any breastfeeding before six months. In addition, exposure during pregnancy was associated with a shorter duration of breastfeeding and a lower prevalence of breastfeeding. Conclusion: It was found that exposure to passive smoking during pregnancy was associated with interruption or a lower frequency of breastfeeding, both in exclusive breastfeeding and in other periods, compared to the absence of exposure to passive smoking during pregnancy. pregnancy. However, higher quality research is strongly recommended in order to identify greater results.